Interventions : a life in war and peace - Annan, Kofi A. (Kofi Atta); Mousavizadeh, Nader (New York : Penguin Press, 2012)
With eloquence and immediacy, Annan writes about the highs and lows of his years at the United Nations: from shuttle-diplomacy during crises such as Kosovo, Lebanon and Israel-Palestine to the wrenching battles over the Iraq War to the creation of the landmark Responsibility to Protect doctrine.
Preface: The arc of intervention -- Prologue: Peacekeeper, peacemaker -- Independence: African beginnings -- Promises to keep: Somalia, Rwanda, Bosnia, and the trials of peacekeeping in a world of civil war -- Sovereignty and human rights: Kosovo, East Timor, Darfur, and the responsibility to protect -- A peoples' United Nations: reforming global governance and restoring the rule of law -- The fate of the continent: Africa's wars, Africa's peace -- Redefining human security: the global fight against poverty and the millennium development goals --The world's fault line: peacemaking in the Middle East -- The wars of 9/11: terror, Afghanistan, Iraq, and the United Nations at the brink -- Epilogue: Dreams of a realist.
Includes index.
Keywords: Annan, Kofi A; Since 1989; World politics -- 1989-; Statesmen -- Ghana -- Biography; INTERNATIONAL ORGANIZATIONS; WORLD POLITICS; Ghana; Autobiography